Case reportPachydermodactyly – a case report - Rachowska, Regina; Filipowska-Grońska, Agata; Weryńska-Kalemba, Maria; Bożek, Andrzej; Filipowska, Barbara; Zajęcki, Wojciech; Ilczuk, Danuta; Herba, Monika; Jarząb, Jerzy (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2010)
Pachydermodactyly (PDD) is a rare, benign form of digital fibromatosis. It is characterized by symmetrical fusiform soft tissue swelling around the digits of the hand. Mostly it affects the skin of the lateral aspects of the proximal interphalangeal joints of fingers II-IV of young adolescent males. It has been suggested that repeated mechanical trauma leads to the development of this cutaneous thickening. The rapid clinical recognition of PDD would avoid pointless and expensive diagnostic tests according to the rheumatic condition. There is no effective medical treatment for PDD, only discontinuation of mechanical traumatisation that leads to stopping progression of the disease. We present a case report of a 21-year-old patient with a symmetrical diffuse swelling around the digits of the hand. Based on the clinical picture and characteristic histopathological examination pachydermodactyly was diagnosed. The collected data from anamnesis and outcomes of diagnostic tests are presented, and also similar cases from the literature are discussed.